The effect of Knowledge And Attitude Of Ambulance Driver for Improving Defensive Driving Behavior - Fahlevi, Zamzam; chanif, chanif; Safitri, Dwi Nur Rahmantika Puji (South East Asia Nursing Research, 2022)
Defensive driving is a safe driving technique and applies all means to avoid or avoid accidents. Ambulance drivers to master the implementation of defensive driving there are many factors, one of which is knowledge and attitude. The objective of this research is to determine the relationship between knowledge and attitudes with the practice of pre-hospital ambulance drivers regarding defensive driving. This research uses the analytical survey method with a cross-sectional approach with a total sampling technique of 46 ambulance drivers and analyzed using Spearman Rank. Knowledge with a p-value of 0.032 and a correlation coefficient of 0.317*. Attitude with a p-value of 0.019 and a correlation coefficient of 0.345*. There is a significant relationship between knowledge and the practice of defensive driving for ambulance drivers and the higher the knowledge, the better the practice. There is a relationship between attitudes and the practice of defensive driving for ambulance drivers and the more supportive the attitude, the better the practice will be. Further researchers are advised to examine the factors that influence the behavior of ambulance drivers regarding defensive driving.